PEMANFAATAN SAMPAH ORGANIK KAMPUS SEBAGAI UPAYA PENINGKATAN PENDAPATAN KELUARGA CLEANING SERVICE FAKULTAS PERTANIAN UNIVERSITAS JAMBI - Jasminarni; Evita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2021)
Abstract The activity aims to improve facility care knowledge and skills on Faculty of Agriculture Jambi University through education, discussion, training, demonstration and assistance during organic waste processing in campus into compost and package it, so it can increase family income. Problems and the priority to solve the problem are: 1) Lack of adequate work equipment 2) Lack of knowledge about the impact of waste burning to the environment, 3) Lack of knowledge of how to process organic waste into compost, 4) Lack of knowledge about the benefits of organic fertilizers and 5) Lack of knowledge about the added value of organic waste as a source of increased family income. The methods of implementing activities are: 1) Education about the adverse impact of burning waste to the environment, 2) Demonstration about campus organic waste proceesing into compost using Compost Bag, 3) Making compost packaging so it gives value and can increase family income and 5) Assistance in the utilization of compost to plant vegetable and ornamental plants around the Faculty of Agriculture Jambi University. The results of this devotional activity can be seen from the work of partner groups in cultivating organic vegetables, increasing the interest of facility care group of the Faculty of Agriculture, Jambi University to produce organic vegetable products by utilizing the compost that they produce together. Abstract Kegiatan bertujuan meningkatkan pengetahuan dan ketrampilan cleaning service Fakultas Pertanian UNJA melalui penyuluhan, diskusi, pelatihan, demontrasi dan pendampingan teknik pengolahan sampah organik di lingkungan kampus menjadi kompos dan pengemasannya, sehingga dapat meningkatkan pendapatan keluarga. Permasalahan dan skala prioritas penanganan masalahnya adalah : 1) Kurangnya peralatan kerja yang memadai 2) Kurangnya pengetahuan tentang dampak pembakaran sampah terhadap lingkungan, 3) Kurangnya pengetahuan cara pengolahan sampah organik menjadi kompos, 4) Kurangnya pengetahuan tentang manfaat pupuk organik dan 5) Kurangnya pengetahuan tentang nilai tambah sampah organik sebagai sumber peningkatan pendapatan keluarga.Metode pelaksanaan kegiatan adalah : 1) Penyuluhan tentang dampak kurang baik dari pembakaran sampah terhadap lingkungan, 2) Demontrasi pengolahan sampah organik kampus menjadi kompos menggunakan Kompos Bag, 3) Pembuatan kemasan kompos sehingga mempunyai nilai jual dan dapat menambah penghasilan keluarga dan 5) Pendampingan pemanfaatan kompos ke tanaman sayuran dan tanaman hias disekitar lingkungan Fakultas Pertanian UNJA. Hasil dari Kegiatan pengabdian ini dapat dilihat dari hasil kerja kelompok mitra dalam membudidayakan sayuran organik, peningkatan animo anggota kelompok Cleaning Service Fakultas Pertanian Universitas Jambi untuk bersama-sama menghasilkan produk sayuran organik dengan memanfaatkan kompos yang mereka hasilkan.